Structural Design and Multi-Objective Evaluation of Composite Bladed Propeller. Issue 3 (March 2014) - Hong, Y.; Hao, L.F.; Wang, P.C.; Liu, W.B.; Zhang, H.M.; Wang, R.G.
This paper describes the work to design a composite bladed marine propeller. The hydrodynamic load and the nonlinear structural responses are predicted by the coupled FEM/CFD method. A pre-twist strategy is used to determine a new geometry of the composite bladed propeller for improving the hydrodynamic performance. Different material schemes and symmetric stacking sequences are considered as the design parameters. An evaluation method of multi-objective function is presented for optimizing the strength, deflection and mass at design conditions. Numerical results are obtained and the optimal design scheme of the composite bladed propeller is obtained.